K8Ce2I18O53: a novel potassium cerium(iv) iodate with enhanced visible light driven photocatalytic activity resulting from polar zero dimensional [Ce(IO3)8]4− units. Issue 13 (16th March 2017) - Wu, Ruofei; Jiang, Xingxing; Xia, Mingjun; Liu, Lijuan; Wang, Xiaoyang; Lin, Zheshuai; Chen, Chuangtian
Abstract : K8 Ce2 I18 O53 shows the highest visible light driven photocatalytic activity among rare earth iodates due to asynergistic effect between the narrow band gap and polar zero-dimensional [Ce(IO3 )8 ] 4− units. Abstract : Hydrothermally grown iodate, K8 Ce2 I18 O53, featuring polar 0D [Ce(IO3 )8 ] 4− units, has shown the highest visible light driven (VLD) photocatalytic activity in metal iodates reported before. The enhanced VLD photocatalytic property results from a synergistic effect between the narrow band gap and polar 0D [Ce(IO3 )8 ] 4− units, as confirmed using first principles calculations.